Popular signage and visual design: A comunicational artistic perspective (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This research analyzed the functionalities of the popular sign in visual communication, highlighting its evolution and historical permanence. Thus, the impact of the popular sign as a communicational and aesthetic element within the urban landscape was examined, highlighting its identity function and its relationship with graphic and typographic design. Through a qualitative and descriptive approach, lettering in the popular signage of the city of Latacunga was studied, through the Panofsky method to analyze its visual, symbolic and contextual characteristics. Finally, typographies, colors, ornaments and decorative styles used in traditional signage were identified, being significant patterns and similarities that highlight the importance of popular signage as graphic heritage in the face of the challenges of the digital age, as well as the aesthetic influence on contemporary visual culture.
Keywords: Signage; lettering; visual design; local aesthetics; popular graphics